Type 2 diabetes and anxiety symptoms: a cross-sectional study in Peru - Arteaga Zarate, María de Guadalupe (2021)
Objective: To determine the association between diabetes mellitus type 2 and anxiety symptoms using a population-based study from the semi urban population of Tumbes, Peru. Research design and methods: The present study was an observational, analytical cross-sectional one. Data from a population-based study conducted in Tumbes, Peru between 2016 and 2017 was analyzed. The variables studied were T2DM, defined using fasting glucose and anxiety symptoms, using the Goldberg scale. Results: Data from 1609 individuals was analyzed, with mean age 48.16 (SD:10.61) and 810 women (50.3%), where a total of 161 were classified as having T2DM (10.0%; CI 95%: 8.5%-11.4%) and 675 individuals had anxiety symptoms (41.95%; CI 95%:39.5%-44.3%). A statistically significant association was found between DM2 and anxiety symptoms (p <0.001). Furthermore, those patients aware of their diagnosis of diabetes over 5 years had a 56% (95% CI: 25% - 96%) higher prevalence of anxiety symptoms compared to participants without DM2. Conclusion: An association was found between DM2 and anxiety symptoms; there being a higher prevalence of anxiety symptoms in participants previously aware of having DM2. Periodic monitoring of anxiety symptoms is recommended in these patients.